Gradient core-shell structure coaxial electrospun composite fiber material and preparation method thereof
Patent Information
- Application Number
- CN202611073521.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-20
- Publication Date
- 2026-10-27
AI Technical Summary
然而,现有吸波材料及其制备方法仍存在诸多不足,制约了其在实际工程中的进一步应用
[0028]1、本发明提出的梯度核壳结构同轴静电纺丝复合纤维材料,采用核-多层壳梯度结构,核层为碳化PAN/CNTs(碳纳米管质量分数5%~10%),构建连续导电网络,提供高效介电损耗;壳层由内至外依次为Fe3O4@SiO2复合层、TiO2过渡层及PDA表面修饰层,通过复合层引入磁滞损耗和自然共振,过渡层实现阻抗梯度过渡及表面修饰层实现界面极化多重损耗机制;在2 mm厚度下,2 GHz、18 GHz和40 GHz处反射损耗能够达到-12.5 dB、-25.3 dB和-18.6 dB,覆盖低频至毫米波段,显著拓宽有效吸收带宽。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of electromagnetic wave absorbing materials technology, and in particular to gradient core-shell structured coaxial electrospun composite fiber materials and their preparation methods. Background Technology
[0002] Microwave-absorbing materials have wide applications in radar stealth, electromagnetic interference protection, and microwave anechoic chambers. Currently, common microwave-absorbing materials mainly include ferrites, carbon-based composites, and magnetic metal-based materials, and their preparation processes involve techniques such as electrospinning, multilayer coating, or assembly. However, existing microwave-absorbing materials and their preparation methods still have many shortcomings, which restrict their further application in practical engineering.
[0003] Regarding material properties, existing microwave absorbing materials mainly suffer from the following problems: First, narrow absorption bandwidth. The absorption efficiency of traditional ferrites and carbon-based composite materials decreases significantly in the low-frequency (2–6 GHz) and high-frequency (12–18 GHz) bands. The effective bandwidth under the condition of reflection loss ≤-10 dB is usually less than 10 GHz, which is difficult to meet the requirements of broadband stealth. Second, poor impedance matching performance. Single-component or homogeneous materials cannot simultaneously achieve a reasonable match between dielectric constant and magnetic permeability, resulting in a large amount of electromagnetic wave reflection on the material surface. The reflectivity is often higher than 30%, reducing the absorption efficiency. Third, high density. The density of magnetic metal-based microwave absorbing materials is generally greater than 3.0 g / cm³, which is not conducive to the lightweight design of aerospace equipment. Fourth, insufficient mechanical properties. Although carbon-based composite materials have the advantage of being lightweight, their mechanical strength is low, making it difficult to withstand structural loads and unable to achieve integrated structural-functional applications.
[0004] In terms of fabrication processes, existing technologies also have significant shortcomings. On the one hand, when conventional electrospinning techniques are used to prepare core-shell structured fibers, the shell thickness uniformity is poor and component segregation is prone to occur, leading to a weakening of the interfacial polarization effect and affecting the microwave absorption performance. On the other hand, existing core-shell structures are mostly bilayer or homogeneous multilayer structures, lacking a continuous gradient change from the core to the shell, making it difficult to achieve broadband impedance matching; moreover, the fabrication of multilayer gradient structures often requires multiple coating or assembly processes, which are complex, inefficient, and have poor interlayer bonding, affecting the overall reliability and service life of the material. Therefore, there is an urgent need in this field to develop a gradient core-shell structured coaxial electrospun composite fiber material and its preparation method. Summary of the Invention
[0005] The purpose of this invention is to address the shortcomings of existing technologies by proposing a gradient core-shell structure coaxial electrospun composite fiber material and its preparation method.
[0006] Gradient core-shell structured coaxial electrospun composite fiber material, including core and shell layers.
[0007] The core layer is composed of carbonized polyacrylonitrile and uniformly dispersed carbon nanotubes.
[0008] The shell consists of, from the inside out, a dispersion layer composed of magnetic Fe3O4@SiO2 nanoparticles, a transition layer composed of TiO2 dielectric ceramics, and a surface modification layer composed of polydopamine.
[0009] The core layer has a diameter of 0.3 to 0.5 mm, and its diameter accounts for 15% to 30% of the total diameter of the composite fiber material.
[0010] Preferably, the thickness of the dispersion layer is not less than the thickness of the transition layer, and the thickness of the transition layer is not less than the thickness of the surface modification layer.
[0011] Preferably, the ratio of the thickness of the dispersion layer, the thickness of the transition layer, and the thickness of the modification layer is 5:(3-2):(2-1).
[0012] Preferably, the Fe3O4@SiO2 nanoparticles have a particle size of 50–100 nm and the SiO2 coating layer thickness is 5–10 nm.
[0013] Preferably, the mass fraction of carbon nanotubes in the core layer is 5% to 10%.
[0014] Preferably, a method for preparing a gradient core-shell structured coaxial electrospun composite fiber material includes the following steps:
[0015] Step 1, Preparation of core spinning solution: Dissolve 10g of polyacrylonitrile and 5-11g of carbon nanotubes in 86-91g of DMF, and obtain the solution after ultrasonic dispersion and vacuum degassing.
[0016] Step 2: Preparation of shell spinning solution:
[0017] Dispersion layer: 12.3-27.8g of Fe3O4@SiO2 nanoparticles were dispersed in a mixed solvent of 11.1g PVP / 100g DMF and magnetically stirred for 20-24h.
[0018] Transition layer liquid: 5.8–12.3 g TiO2 nanoparticles were mixed with a mixed solvent of 11.1 g PVP / 100 g DMF;
[0019] Surface modification layer solution: Dissolve 1-3.1g of dopamine hydrochloride in 100g of Tris-HCl buffer (pH=8.5) and stir for 5-7h to form PDA solution;
[0020] Step 3: Coaxial electrospinning: Electrospinning is performed using a four-channel coaxial needle.
[0021] Step 4: Heat treatment: The electrospun fibers obtained in Step 3 are subjected to heat treatment, which includes pre-oxidation and carbonization.
[0022] Pre-oxidation treatment: treatment temperature 270~290℃, treatment time 1.5~2.5h, heating rate 2℃ / min, carried out in air;
[0023] Carbonization treatment: treatment temperature 780~850℃, treatment time 0.8~1.5h, heating rate 5℃ / min, carried out under argon protection.
[0024] Preferably, in step 1, the ultrasonic dispersion treatment conditions are 40 kHz and the treatment time is 3 to 5 hours; the vacuum degassing treatment conditions are -0.1 MPa and the treatment time is 1.5 to 2.5 hours.
[0025] Preferably, in step 2, the TiO2 crystal form is anatase, and the TiO2 particle size is 20-30 nm.
[0026] Preferably, in step 3, the flow rate of the core spinning solution is 0.8–1.2 mL / h; the flow rate of the dispersion layer solution is 2.3–2.8 mL / h; the flow rate of the transition layer solution is 1.8–2.2 mL / h; the flow rate of the surface modification layer solution is 1.3–1.8 mL / h; the receiving distance is 15–20 cm; and the voltage is 15–25 kV.
[0027] The beneficial effects of this invention are:
[0028] 1. The gradient core-shell structure coaxial electrospun composite fiber material proposed in this invention adopts a core-multilayer shell gradient structure. The core layer is carbonized PAN / CNTs (carbon nanotube mass fraction 5%~10%), which constructs a continuous conductive network and provides high-efficiency dielectric loss. The shell layer consists of an Fe3O4@SiO2 composite layer, a TiO2 transition layer and a PDA surface modification layer from the inside to the outside. The composite layer introduces hysteresis loss and natural resonance, the transition layer realizes impedance gradient transition and the surface modification layer realizes the interface polarization multiple loss mechanism. With a thickness of 2 mm, the reflection loss at 2 GHz, 18 GHz and 40 GHz can reach -12.5 dB, -25.3 dB and -18.6 dB, respectively, covering the low frequency to millimeter wave band and significantly broadening the effective absorption bandwidth.
[0029] 2. The gradient core-shell structure coaxial electrospun composite fiber material proposed in this invention has a density of less than 1.15 g / cm³, which is more than 60% lower than that of traditional magnetic metal matrix materials, meeting the requirements for lightweighting in aerospace. At the same time, the PDA outer shell layer increases the bonding strength between the fiber and the matrix by 3 times, improving structural reliability.
[0030] 3. The gradient core-shell structure coaxial electrospun composite fiber material proposed in this invention can achieve a continuous gradient change in shell thickness by controlling the shell flow rate gradient, which is beneficial for the stable preparation of broadband absorption materials. Detailed Implementation
[0031] The present invention will be further explained below with reference to specific embodiments.
[0032] In Example 1, the gradient core-shell structure coaxial electrospun composite fiber material includes a core layer and a shell layer.
[0033] The core layer consists of carbonized polyacrylonitrile and uniformly dispersed carbon nanotubes;
[0034] The shell consists of, from the inside out, a dispersion layer composed of magnetic Fe3O4@SiO2 nanoparticles, a transition layer composed of TiO2 dielectric ceramics, and a surface modification layer composed of polydopamine.
[0035] The core layer has a diameter of 0.3 mm, which accounts for 15% of the total diameter of the composite fiber material.
[0036] The thickness of the dispersion layer is not less than the thickness of the transition layer, and the thickness of the transition layer is not less than the thickness of the surface modification layer.
[0037] The ratio of the thickness of the dispersion layer, the thickness of the transition layer, and the thickness of the modification layer is 5:3:2.
[0038] The Fe3O4@SiO2 nanoparticles have a particle size of 50 nm and a SiO2 coating thickness of 5 nm.
[0039] The mass fraction of carbon nanotubes in the core layer is 5%.
[0040] A method for preparing a gradient core-shell structured coaxial electrospun composite fiber material includes the following steps:
[0041] Step 1, Preparation of core spinning solution: Dissolve 10g of polyacrylonitrile and 5g of carbon nanotubes in 86g of DMF, and obtain the solution after ultrasonic dispersion and vacuum degassing.
[0042] Step 2: Preparation of shell spinning solution:
[0043] Dispersion layer: 12.3g Fe3O4@SiO2 nanoparticles were dispersed in a mixed solvent of 11.1g PVP / 100g DMF and magnetically stirred for 20h;
[0044] Transition layer liquid: 5.8g TiO2 nanoparticles were mixed with a mixed solvent of 11.1g PVP / 100g DMF;
[0045] Surface modification layer solution: Dissolve 1g of dopamine hydrochloride in 100g of Tris-HCl buffer (pH=8.5), stir and polymerize for 5h to form PDA solution;
[0046] Step 3: Coaxial electrospinning: Electrospinning is performed using a four-channel coaxial needle.
[0047] Step 4: Heat treatment: The electrospun fibers obtained in Step 3 are subjected to heat treatment, which includes pre-oxidation and carbonization.
[0048] Pre-oxidation treatment: treatment temperature 270℃, treatment time 1.5h, heating rate 2℃ / min, carried out in air;
[0049] Carbonization treatment: treatment temperature 780℃, treatment time 0.8h, heating rate 5℃ / min, carried out under argon protection.
[0050] In step 1, the ultrasonic dispersion treatment conditions are 40 kHz and the treatment time is 3 to 5 h; the vacuum degassing treatment conditions are -0.1 MPa and the treatment time is 1.5 h.
[0051] In step 2, the TiO2 crystal form is anatase phase, and the TiO2 particle size is 20 nm.
[0052] In step 3, the flow rate of the core spinning solution is 0.8 mL / h; the flow rate of the dispersion layer solution is 2.3 mL / h; the flow rate of the transition layer solution is 1.8 mL / h; the flow rate of the surface modification layer solution is 1.3 mL / h; the receiving distance is 15 cm; and the voltage is 15 kV.
[0053] In Example 2, the gradient core-shell structure coaxial electrospun composite fiber material includes a core layer and a shell layer.
[0054] The core layer consists of carbonized polyacrylonitrile and uniformly dispersed carbon nanotubes;
[0055] The shell consists of, from the inside out, a dispersion layer composed of magnetic Fe3O4@SiO2 nanoparticles, a transition layer composed of TiO2 dielectric ceramics, and a surface modification layer composed of polydopamine.
[0056] The core layer has a diameter of 0.5 mm, which accounts for 30% of the total diameter of the composite fiber material.
[0057] The thickness of the dispersion layer is not less than the thickness of the transition layer, and the thickness of the transition layer is not less than the thickness of the surface modification layer.
[0058] The ratio of the thickness of the dispersion layer, the thickness of the transition layer, and the thickness of the modification layer is 5:2:1.
[0059] The Fe3O4@SiO2 nanoparticles have a particle size of 100 nm and a SiO2 coating thickness of 10 nm.
[0060] The mass fraction of carbon nanotubes in the core layer is 10%.
[0061] A method for preparing a gradient core-shell structured coaxial electrospun composite fiber material includes the following steps:
[0062] Step 1, Preparation of core spinning solution: Dissolve 10g of polyacrylonitrile and 11g of carbon nanotubes in 86g of DMF, and obtain the solution after ultrasonic dispersion and vacuum degassing.
[0063] Step 2: Preparation of shell spinning solution:
[0064] Dispersion layer: 27.8g Fe3O4@SiO2 nanoparticles were dispersed in a mixed solvent of 11.1g PVP / 100g DMF and magnetically stirred for 24h.
[0065] Transition layer liquid: 12.3g TiO2 nanoparticles were mixed with a mixed solvent of 11.1g PVP / 100g DMF;
[0066] Surface modification layer solution: Dissolve 1g to 3.1g of dopamine hydrochloride in 100g of Tris-HCl buffer (pH=8.5) and stir for 7h to form PDA solution;
[0067] Step 3: Coaxial electrospinning: Electrospinning is performed using a four-channel coaxial needle.
[0068] Step 4: Heat treatment: The electrospun fibers obtained in Step 3 are subjected to heat treatment, which includes pre-oxidation and carbonization.
[0069] Pre-oxidation treatment: treatment temperature 290℃, treatment time 2.5h, heating rate 2℃ / min, carried out in air;
[0070] Carbonization treatment: The treatment temperature is 850℃, the treatment time is 1.5h, the heating rate is 5℃ / min, and the treatment is carried out under argon protection.
[0071] In step 1, the ultrasonic dispersion treatment conditions are 40 kHz and the treatment time is 5 h; the vacuum degassing treatment conditions are -0.1 MPa and the treatment time is 2.5 h.
[0072] In step 2, the TiO2 crystal form is anatase phase, and the TiO2 particle size is 30 nm.
[0073] In step 3, the flow rate of the core spinning solution is 1.2 mL / h; the flow rate of the dispersion layer solution is 2.8 mL / h; the flow rate of the transition layer solution is 2.2 mL / h; the flow rate of the surface modification layer solution is 1.8 mL / h; the receiving distance is 20 cm; and the voltage is 25 kV.
[0074] In Example 3, the gradient core-shell structure coaxial electrospun composite fiber material includes a core layer and a shell layer.
[0075] The core layer consists of carbonized polyacrylonitrile and uniformly dispersed carbon nanotubes;
[0076] The shell consists of, from the inside out, a dispersion layer composed of magnetic Fe3O4@SiO2 nanoparticles, a transition layer composed of TiO2 dielectric ceramics, and a surface modification layer composed of polydopamine.
[0077] The core layer has a diameter of 0.4 mm, which accounts for 25% of the total diameter of the composite fiber material.
[0078] The thickness of the dispersion layer is not less than the thickness of the transition layer, and the thickness of the transition layer is not less than the thickness of the surface modification layer.
[0079] The ratio of the thickness of the dispersion layer, the thickness of the transition layer, and the thickness of the modification layer is 5:2.5:1.5.
[0080] The Fe3O4@SiO2 nanoparticles have a particle size of 80 nm and a SiO2 coating thickness of 8 nm.
[0081] The mass fraction of carbon nanotubes in the core layer is 7%.
[0082] A method for preparing a gradient core-shell structured coaxial electrospun composite fiber material includes the following steps:
[0083] Step 1, Preparation of core spinning solution: Dissolve 10g of polyacrylonitrile and 8g of carbon nanotubes in 86g of DMF, and obtain the solution after ultrasonic dispersion and vacuum degassing.
[0084] Step 2: Preparation of shell spinning solution:
[0085] Dispersion layer: 23g Fe3O4@SiO2 nanoparticles were dispersed in a mixed solvent of 11.1g PVP / 100g DMF and magnetically stirred for 22h;
[0086] Transition layer liquid: 8g TiO2 nanoparticles were mixed with a mixed solvent of 11.1g PVP / 100g DMF;
[0087] Surface modification layer solution: Dissolve 2.5g dopamine hydrochloride in 100g Tris-HCl buffer (pH=8.5), stir and polymerize for 6h to form PDA solution;
[0088] Step 3: Coaxial electrospinning: Electrospinning is performed using a four-channel coaxial needle.
[0089] Step 4: Heat treatment: The electrospun fibers obtained in Step 3 are subjected to heat treatment, which includes pre-oxidation and carbonization.
[0090] Pre-oxidation treatment: treatment temperature 280℃, treatment time 2h, heating rate 2℃ / min, carried out in air;
[0091] Carbonization treatment: The treatment temperature is 800℃, the treatment time is 1h, the heating rate is 5℃ / min, and the treatment is carried out under argon protection.
[0092] In step 1, the ultrasonic dispersion treatment conditions are 40 kHz and the treatment time is 4 h; the vacuum degassing treatment conditions are -0.1 MPa and the treatment time is 2 h.
[0093] In step 2, the TiO2 crystal form is anatase phase, and the TiO2 particle size is 25 nm.
[0094] In step 3, the flow rate of the core spinning solution is 1 mL / h; the flow rate of the dispersion layer solution is 2.5 mL / h; the flow rate of the transition layer solution is 2 mL / h; the flow rate of the surface modification layer solution is 1.5 mL / h; the receiving distance is 18 cm; and the voltage is 20 kV.
[0095] In Example 4, the gradient core-shell structured coaxial electrospun composite fiber material includes a core layer and a shell layer.
[0096] The core layer consists of carbonized polyacrylonitrile and uniformly dispersed carbon nanotubes;
[0097] The shell consists of, from the inside out, a dispersion layer composed of magnetic Fe3O4@SiO2 nanoparticles, a transition layer composed of TiO2 dielectric ceramics, and a surface modification layer composed of polydopamine.
[0098] The core layer has a diameter of 0.3 mm, which accounts for 15% of the total diameter of the composite fiber material.
[0099] The thickness of the dispersion layer is not less than the thickness of the transition layer, and the thickness of the transition layer is not less than the thickness of the surface modification layer.
[0100] The ratio of the thickness of the dispersion layer, the thickness of the transition layer, and the thickness of the modification layer is 5:3:2.
[0101] The Fe3O4@SiO2 nanoparticles have a particle size of 50 nm and a SiO2 coating thickness of 5 nm.
[0102] The mass fraction of carbon nanotubes in the core layer is 5%.
[0103] A method for preparing a gradient core-shell structured coaxial electrospun composite fiber material includes the following steps:
[0104] Step 1, Preparation of core spinning solution: Dissolve 10g of polyacrylonitrile and 11g of carbon nanotubes in 86g of DMF, and obtain the solution after ultrasonic dispersion and vacuum degassing.
[0105] Step 2: Preparation of shell spinning solution:
[0106] Dispersion layer: 27.8g Fe3O4@SiO2 nanoparticles were dispersed in a mixed solvent of 11.1g PVP / 100g DMF and magnetically stirred for 24h.
[0107] Transition layer liquid: 12.3g TiO2 nanoparticles were mixed with a mixed solvent of 11.1g PVP / 100g DMF;
[0108] Surface modification layer solution: Dissolve 1g to 3.1g of dopamine hydrochloride in 100g of Tris-HCl buffer (pH=8.5) and stir for 7h to form PDA solution;
[0109] Step 3: Coaxial electrospinning: Electrospinning is performed using a four-channel coaxial needle.
[0110] Step 4: Heat treatment: The electrospun fibers obtained in Step 3 are subjected to heat treatment, which includes pre-oxidation and carbonization.
[0111] Pre-oxidation treatment: treatment temperature 290℃, treatment time 2.5h, heating rate 2℃ / min, carried out in air;
[0112] Carbonization treatment: The treatment temperature is 850℃, the treatment time is 1.5h, the heating rate is 5℃ / min, and the treatment is carried out under argon protection.
[0113] In step 1, the ultrasonic dispersion treatment conditions are 40 kHz and the treatment time is 5 h; the vacuum degassing treatment conditions are -0.1 MPa and the treatment time is 2.5 h.
[0114] In step 2, the TiO2 crystal form is anatase phase, and the TiO2 particle size is 30 nm.
[0115] In step 3, the flow rate of the core spinning solution is 1.2 mL / h; the flow rate of the dispersion layer solution is 2.8 mL / h; the flow rate of the transition layer solution is 2.2 mL / h; the flow rate of the surface modification layer solution is 1.8 mL / h; the receiving distance is 20 cm; and the voltage is 25 kV.
[0116] In Example 5, the gradient core-shell structured coaxial electrospun composite fiber material includes a core layer and a shell layer.
[0117] The core layer consists of carbonized polyacrylonitrile and uniformly dispersed carbon nanotubes;
[0118] The shell consists of, from the inside out, a dispersion layer composed of magnetic Fe3O4@SiO2 nanoparticles, a transition layer composed of TiO2 dielectric ceramics, and a surface modification layer composed of polydopamine.
[0119] The core layer has a diameter of 0.3 mm, which accounts for 15% of the total diameter of the composite fiber material.
[0120] The thickness of the dispersion layer is not less than the thickness of the transition layer, and the thickness of the transition layer is not less than the thickness of the surface modification layer.
[0121] The ratio of the thickness of the dispersion layer, the thickness of the transition layer, and the thickness of the modification layer is 5:3:2.
[0122] The Fe3O4@SiO2 nanoparticles have a particle size of 50 nm and a SiO2 coating thickness of 5 nm.
[0123] The mass fraction of carbon nanotubes in the core layer is 5%.
[0124] A method for preparing a gradient core-shell structured coaxial electrospun composite fiber material includes the following steps:
[0125] Step 1, Preparation of core spinning solution: Dissolve 10g of polyacrylonitrile and 8g of carbon nanotubes in 86g of DMF, and obtain the solution after ultrasonic dispersion and vacuum degassing.
[0126] Step 2: Preparation of shell spinning solution:
[0127] Dispersion layer: 23g Fe3O4@SiO2 nanoparticles were dispersed in a mixed solvent of 11.1g PVP / 100g DMF and magnetically stirred for 22h;
[0128] Transition layer liquid: 8g TiO2 nanoparticles were mixed with a mixed solvent of 11.1g PVP / 100g DMF;
[0129] Surface modification layer solution: Dissolve 2.5g dopamine hydrochloride in 100g Tris-HCl buffer (pH=8.5), stir and polymerize for 6h to form PDA solution;
[0130] Step 3: Coaxial electrospinning: Electrospinning is performed using a four-channel coaxial needle.
[0131] Step 4: Heat treatment: The electrospun fibers obtained in Step 3 are subjected to heat treatment, which includes pre-oxidation and carbonization.
[0132] Pre-oxidation treatment: treatment temperature 280℃, treatment time 2h, heating rate 2℃ / min, carried out in air;
[0133] Carbonization treatment: The treatment temperature is 800℃, the treatment time is 1h, the heating rate is 5℃ / min, and the treatment is carried out under argon protection.
[0134] In step 1, the ultrasonic dispersion treatment conditions are 40 kHz and the treatment time is 4 h; the vacuum degassing treatment conditions are -0.1 MPa and the treatment time is 2 h.
[0135] In step 2, the TiO2 crystal form is anatase phase, and the TiO2 particle size is 25 nm.
[0136] In step 3, the flow rate of the core spinning solution is 1 mL / h; the flow rate of the dispersion layer solution is 2.5 mL / h; the flow rate of the transition layer solution is 2 mL / h; the flow rate of the surface modification layer solution is 1.5 mL / h; the receiving distance is 18 cm; and the voltage is 20 kV.
[0137] The gradient core-shell structure coaxial electrospun composite fiber materials from Examples 1-5 were made into standard flat plate samples. According to the GJB 2038A-2011 standard, frequency sweep tests were conducted in a microwave anechoic chamber using the bow method or a vector network analyzer to test their reflection loss and density at 2 GHz, 18 GHz, and 40 GHz. The test results are shown in Table 1.
[0138]
[0139] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.
Claims
1. A gradient core-shell structured coaxial electrospun composite fiber material, characterized in that, Including the core and shell, The core layer is composed of carbonized polyacrylonitrile and uniformly dispersed carbon nanotubes. The shell consists of, from the inside out, a dispersion layer composed of magnetic Fe3O4@SiO2 nanoparticles, a transition layer composed of TiO2 dielectric ceramics, and a surface modification layer composed of polydopamine. The core layer has a diameter of 0.3 to 0.5 mm, and its diameter accounts for 15% to 30% of the total diameter of the composite fiber material.
2. The gradient core-shell structured coaxial electrospun composite fiber material according to claim 1, characterized in that, The thickness of the dispersion layer is not less than the thickness of the transition layer, and the thickness of the transition layer is not less than the thickness of the surface modification layer.
3. The gradient core-shell structured coaxial electrospun composite fiber material according to claim 2, characterized in that, The ratio of the thickness of the dispersion layer, the thickness of the transition layer, and the thickness of the modification layer is 5:(3-2):(2-1).
4. The gradient core-shell structured coaxial electrospun composite fiber material according to claim 1, characterized in that, The Fe3O4@SiO2 nanoparticles have a particle size of 50–100 nm and a SiO2 coating thickness of 5–10 nm.
5. The gradient core-shell structured coaxial electrospun composite fiber material according to claim 1, characterized in that, The mass fraction of carbon nanotubes in the core layer is 5% to 10%.
6. A method for preparing a gradient core-shell structured coaxial electrospun composite fiber material according to any one of claims 1-5, characterized in that, Includes the following steps: Step 1, Preparation of core spinning solution: Dissolve 10g of polyacrylonitrile and 5-11g of carbon nanotubes in 86-91g of DMF, and obtain the solution after ultrasonic dispersion and vacuum degassing. Step 2: Preparation of shell spinning solution: Dispersion layer: 12.3-27.8g of Fe3O4@SiO2 nanoparticles were dispersed in a mixed solvent of 11.1g PVP / 100g DMF and magnetically stirred for 20-24h. Transition layer liquid: 5.8–12.3 g TiO2 nanoparticles were mixed with a mixed solvent of 11.1 g PVP / 100 g DMF; Surface modification layer solution: Dissolve 1g to 3.1g of dopamine hydrochloride in 100g of Tris-HCl buffer (pH=8.5) and stir for 5 to 7 hours to form a PDA solution. Step 3: Coaxial electrospinning: Electrospinning is performed using a four-channel coaxial needle. Step 4: Heat treatment: The electrospun fibers obtained in Step 3 are subjected to heat treatment, which includes pre-oxidation and carbonization. Pre-oxidation treatment: treatment temperature 270~290℃, treatment time 1.5~2.5h, heating rate 2℃ / min, carried out in air; Carbonization treatment: treatment temperature 780~850℃, treatment time 0.8~1.5h, heating rate 5℃ / min, carried out under argon protection.
7. The method for preparing a gradient core-shell structured coaxial electrospun composite fiber material according to claim 6, characterized in that, In step 1, the ultrasonic dispersion treatment conditions are 40 kHz and the treatment time is 3 to 5 hours; the vacuum degassing treatment conditions are -0.1 MPa and the treatment time is 1.5 to 2.5 hours.
8. The method for preparing a gradient core-shell structured coaxial electrospun composite fiber material according to claim 6, characterized in that, In step 2, the TiO2 crystal form is anatase, and the TiO2 particle size is 20-30 nm.
9. The method for preparing a gradient core-shell structured coaxial electrospun composite fiber material according to claim 6, characterized in that, In step 3, the flow rate of the core spinning solution is 0.8–1.2 mL / h; the flow rate of the dispersion layer solution is 2.3–2.8 mL / h; the flow rate of the transition layer solution is 1.8–2.2 mL / h; the flow rate of the surface modification layer solution is 1.3–1.8 mL / h; the receiving distance is 15–20 cm; and the voltage is 15–25 kV.